(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
In the current study Psychotria dalzellii Hook.f. stem-bark samples were procured from Joida, Western Ghats, Karnataka, India. air-dried and subjected to Soxhlet extraction. The obtained extracts were screened for preliminary phytochemicals which resulted in the existence of flavonoids, alkaloids, glycosides, phenols, tannins, steroids, triterpenoids, saponins, carbohydrates and lignins. Subsequently, the ethanolic stem bark extracts were subjected to GC-MS analysis to quantitatively estimate the phytoconstituents. It reveals the presence of 20 bioactive chemicals. Among them, 2-Furancarboxaldehyde, 5-(hydroxymethyl)- (59.26%); p-Mesyloxyphenol (10.68%); 2-Furaldehyde diethyl acetal (4.54%); 4H-Pyran-4-one, 2,3-dihydro-3,5-dihydroxy-6-methyl (4.11%) were noted to be the principal compounds detected. Furthermore, in-vitro cytotoxic activities on MCF-7 and L929 cell lines were determined by 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide assay. The extract exhibited considerable cytotoxic activity towards MCF-7 cell lines at higher concentrations with an IC50 value of 440.82 µg/ml and it showed very less toxicity towards L929 normal cell lines. Which indicates its potential as a possible source of bioactive constituents for medicinal and pharmaceutical exploration.